2012
DOI: 10.1063/1.3684658
|View full text |Cite
|
Sign up to set email alerts
|

Sub-TeV proton beam generation by ultra-intense laser irradiation of foil-and-gas target

Abstract: A two-phase proton acceleration scheme using an ultra-intense laser pulse irradiating a proton foil with a tenuous heavier-ion plasma behind it is presented. The foil electrons are compressed and pushed out as a thin dense layer by the radiation pressure and propagate in the plasma behind at near the light speed. The protons are in turn accelerated by the resulting space-charge field and also enter the backside plasma, but without the formation of a quasistationary double layer. The electron layer is rapidly w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…In conjunction with the crystal cavities designed for the XFELO, such table-top devices have the potential to become a key tool for the release on demand of energy stored in nuclei at large ion accelerator facilities. Alternatively, the exciting forecast of compact shaped-foil-target ion accelerators [54,55], foil-and-gas target [56] and radiation pressure acceleration [57][58][59][60][61] together with microlens beam focusing [62] are likely to provide a viable table-top solution to be used together with the existing large-scale XFELs. A further study of the overlap efficiency for the laser beams and ion bunches shows that the copropagating laser beams setup is more advantageous.…”
Section: Experimental Facilitiesmentioning
confidence: 99%
“…In conjunction with the crystal cavities designed for the XFELO, such table-top devices have the potential to become a key tool for the release on demand of energy stored in nuclei at large ion accelerator facilities. Alternatively, the exciting forecast of compact shaped-foil-target ion accelerators [54,55], foil-and-gas target [56] and radiation pressure acceleration [57][58][59][60][61] together with microlens beam focusing [62] are likely to provide a viable table-top solution to be used together with the existing large-scale XFELs. A further study of the overlap efficiency for the laser beams and ion bunches shows that the copropagating laser beams setup is more advantageous.…”
Section: Experimental Facilitiesmentioning
confidence: 99%
“…[14][15][16] However, because of transverse instabilities and hole-boring by the laser pulse, [14][15][16][17] the acceleration length is rather limited and it is difficult to enhance proton energy without still higher laser intensity. Recently, it has been shown that tens GeV proton beams 18,19 can be obtained by sequential radiation pressure and bubble acceleration or a moving double-layer, or in a two-phase acceleration regime 20,21 by ultra-relativistic lasers. However, in classical RPA and laser wakefield acceleration (LWFA), 22 the accelerated ion bunch tends to diverge because of the ubiquitous intense space-charge field.…”
Section: Introductionmentioning
confidence: 99%
“…To overcome the problem of large energy spread, several methods, including tailoring the target shape, changing the ion species, multi stage acceleration, have been presented. One of the ways for improving the proton quality is the micro-structured double-layer (DL) target scheme which was proposed by Esirkepov et al [27] and has been widely investigated in both theory and experiment [28][29][30][31][32][33][34][35][36][37][38].…”
Section: Introductionmentioning
confidence: 99%